DESIGN AND IMPLEMENTATION OF A WIRELESS NETWORK SYSTEM IN A SMART CAMPUS - Anwar, Toni; Mui, Wendy Goh Pek (CommIT (Communication and Information Technology) Journal, 2007)
Article talks about the design and implementation of wireless network in Engineering Campus of UniversitySains Malaysia. The goals of this research is designing a network which able to bring mobility to all network usersin this campus. In this research, there is a mathematical model which can be used to predict the coverage of theaccess point. Coverage testing had been carried out at library. Based on the original placement of the access pointwhich done by the PPKT, the Universiti Sains Malaysia’s (USM) computer center. Since the result is not so satisfying,a new design based on the characteristic of the access point and the building structure was done.Keywords: wireless network, smart campus, library